Free speech versus marginalized groups: Public and newspaper responses to the Charlie Hebdo attack. (June 2019) - Liu, Juan; Shafi, Ashik
This study explores how British and American newspapers covered the 2015 terrorist attack on Charlie Hebdo. British newspapers prioritize free speech and the protection of marginalized groups compared with American ones, but both countries differentiate Muslims from radical terrorists. Attention to news media coverage of the attack is positively related to public approval of publishing the cartoons, supporting press freedom. Implications for free speech debate over Charlie Hebdo are discussed.